Indonesia’s Constitutional Foundation Applies the Death Penalty Against the Intermediary for the Sale and Purchase of Narcotics Bandar - Mukti Jaharsa; Yusuf Muhamad Said (LEGAL BRIEF, 2022)
The danger of narcotics use is quite large in its influence on the state, if there is a large-scale use of narcotics in society, then the Indonesian nation will become a sick nation, if this happens the country will be fragile from within because national resilience has declined. This research plays an important role in obtaining accurate and reliable data. Therefore, the research method used as a tool or method for guiding in conducting research is normative juridical, namely analyzing the relationship between applicable laws and regulations with legal theory and practice of implementing positive law in the field regarding the issues discussed. In conclusion, the definition of the right to life as regulated in Article 28 J paragraph (2) of the 1945 Constitution is a right where no one's life may be taken arbitrarily. What is not allowed is "arbitrarily deprivide of his life". Meanwhile, regarding the difference in decisions between the Serang District Court Decision Number 837/Pid.Sus/2020/PN. Srg who decided the death penalty, which was annulled by the decision of the Banten High Court Number 36/PID.SUS/2021/PT BTN), is not a substantive matter, all judges agree on the death penalty, but rather on a matter of belief and a matter of trial technicality such as the number that is still doubtful by the Serang judges, and the elderly age of the defendant.